TRANSFORMASI BIROKRASI MEMPERMUDAH PERIZINAN USAHA DENGAN ONLINE SINGLE SUBMISSION (OSS): Bureaucratic Transformation Simplifies Business Licensing with Online Single Submission (OSS) - Fauzi, Dicky Ahmad (Fakultas Hukum, Universitas Trisakti, 2024)
Thils palper alilms to alnallyze the ilmplementaltilon of the Onlilne Silngle Submilssilon (OSS) wilth ilts aldvalntalges alnd dilsaldvalntalges, als well als the obstalcles iln operaltilng ilt. Thils study uses the socilo legall method, where the legall alspect ils relalted to the ilmplementilng OSS als al form of lilcensilng tralnsformaltilon iln the ilnvestment sector reduces ilnvestment processes alnd procedures iln Ilndonesilal, whilch halve been consildered convoluted, hilgh-cost alnd do not gualralntee legall certalilnty or the malny ilnstiltutilons thalt halve the aluthorilty to ilssue permilts. Whereals the socilall alspect alnallyzes the aldvalntalges of the OSS system iln dilsplalyilng reall tilme daltal from tilme to tilme relalted to busilness alctor daltal, ilnvestor daltal thalt caln be used als al balsils for malkilng al decilsilon. The results shows thalt the constralilnts iln the ilmplementaltilon of OSS alre unstalble ilnternet networks iln some palrts of Ilndonesilal alnd not alll alvalillalble humaln resources who operalte the OSS system iln the regilons, whilch results iln valrilous polilciles malde by locall governments thalt contraldilct the OSS system.